2022
DOI: 10.1371/journal.pdig.0000067
|View full text |Cite
|
Sign up to set email alerts
|

Comparing different versions of computer-aided detection products when reading chest X-rays for tuberculosis

Abstract: Computer-aided detection (CAD) was recently recommended by the WHO for TB screening and triage based on several evaluations, but unlike traditional diagnostic tests, software versions are updated frequently and require constant evaluation. Since then, newer versions of two of the evaluated products have already been released. We used a case control sample of 12,890 chest X-rays to compare performance and model the programmatic effect of upgrading to newer versions of CAD4TB and qXR. We compared the area under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 6 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…Whether these newer versions guarantee enhanced accuracy remains to be determined. Two recent studies compared the performance of newer versions of qXR 14 and CAD4TB 14 , 16 with their predecessors. In both, the updated CAD versions outperformed the preceding products, demonstrating the need for continuous reassessment and objective re-validation of diagnostic accuracy and threshold calibrations.…”
Section: Diagnostic Performance Of Cad For Tbmentioning
confidence: 99%
“…Whether these newer versions guarantee enhanced accuracy remains to be determined. Two recent studies compared the performance of newer versions of qXR 14 and CAD4TB 14 , 16 with their predecessors. In both, the updated CAD versions outperformed the preceding products, demonstrating the need for continuous reassessment and objective re-validation of diagnostic accuracy and threshold calibrations.…”
Section: Diagnostic Performance Of Cad For Tbmentioning
confidence: 99%
“… 2 7 CAD4TB is updated annually, and the 7 th version has been released recently. Screening programmes might be eager to use new versions because studies report improved performance, 8 , 9 but no recommendations on adopting software updates currently exist. Here, we have evaluated the triaging performance characteristics and optimal thresholds of the latest version of CAD4TB (v7) compared to the two most recent versions (v5 and v6).…”
mentioning
confidence: 99%
“…However, importantly, no meta-analyses or pooled estimates of accuracy were performed. Furthermore, observational studies outside of Africa evaluating CAD during active case finding have found the tool to be reasonably accurate (AUC >0.80), equaling or surpassing human reader performance [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%